2019
DOI: 10.1111/cobi.13343
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with and ecosystem function of biodiversity offsets in North American and European freshwaters

Abstract: Land-use change via human development is a major driver of biodiversity loss. To reduce these impacts, billions of dollars are spent on biodiversity offsets. However, studies evaluating offset project effectiveness that examine components such as the overall compliance and function of projects remain rare. We reviewed 577 offsetting projects in freshwater ecosystems that included the metrics project size, type of aquatic system (e.g., wetland and creek), offsetting measure (e.g., enhancement, restoration, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 81 publications
2
38
0
Order By: Relevance
“…Imperfect compliance rates per se do not guarantee failure of NNL policies from an ecological perspective, as the effects of compliance failure might be outweighed by offset multipliers (Bull, Lloyd, & Strange, ). However, a recent global review including gray literature demonstrated that compliance with offset permit criteria often considerably exceeds the ecological functional performance of those offsets, indicating that achieving compliance is often insufficient to achieve NNL (Theis et al., ). Additionally, low compliance rates do indicate that regulatory enforcement of offset outcomes is often lacking, potentially demonstrating limited institutional interest in the true outcomes of offsetting, thus weakening the probability of NNL outcomes (Walker et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Imperfect compliance rates per se do not guarantee failure of NNL policies from an ecological perspective, as the effects of compliance failure might be outweighed by offset multipliers (Bull, Lloyd, & Strange, ). However, a recent global review including gray literature demonstrated that compliance with offset permit criteria often considerably exceeds the ecological functional performance of those offsets, indicating that achieving compliance is often insufficient to achieve NNL (Theis et al., ). Additionally, low compliance rates do indicate that regulatory enforcement of offset outcomes is often lacking, potentially demonstrating limited institutional interest in the true outcomes of offsetting, thus weakening the probability of NNL outcomes (Walker et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Such pecuniary enforcement measures have been demonstrated in the context of other environmental policies to have direct and indirect benefits, such as both increasing compliance rates within punished firms, and inducing spillovers improving compliance within unpunished firms (Gray & Shimshack, ). While improving compliance is likely key, if NNL policies fail to use an appropriate reference system (either the pre‐impact site or control site) to define the compliance criteria for offsets, then even achieving full compliance may well fail to achieve NNL of biodiversity across the paired impacted and offset sites (Theis et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Step 2 is minimization of impacts, for example, via planning or technical solutions. Project impacts seem to be reduced to the level of compliance with environmental regulation (Theis et al 2020), but it is questionable whether businesses are willing to invest substantial extra money into reducing impacts even further. Putting these initial misgivings aside, our main argument here is about the third level of the mitigation hierarchy, local rehabilitation.…”
Section: The Alternate Mitigation Hierarchymentioning
confidence: 99%
“…Lastly, even if conservation interventions are implemented in line with offset obligations, incomplete understanding of restoration ecology or the effectiveness of the implemented offset actions can lead to a failure to achieve NNL in biodiversity or ecosystem function. 32,34,87 The Future of No Net Loss Over the last decade, there has been fierce debate about the merits of NNL and biodiversity offsetting and the degree to which it can help achieve or potentially unintentionally undermine conservation outcomes. 37,88,89 Empirical explorations of unintended outcomes remain scarce and largely inconclusive so far (e.g., no evidence for ''license to trash'' in Levrel et al 51 or Gibbons et al 54 ); nevertheless, there is clearly in some contexts merit to the idea that NNL and offsetting policies have been designed by policymakers and influenced by the private sector to ''sell'' the narrative that infrastructural expansion and environmental protection can go hand in hand 75,90 without deep reflection on the considerable barriers to achieving true NNL in practice or the place-based nature of biodiversity and cultural value.…”
Section: Project-scale Implementation and Compliance Challengesmentioning
confidence: 99%